2012
DOI: 10.1371/journal.pone.0034260
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Blind Beetles in Isolated Aquifers: A Test of Alternative Modes of Speciation

Abstract: Evidence is growing that not only allopatric but also sympatric speciation can be important in the evolution of species. Sympatric speciation has most convincingly been demonstrated in laboratory experiments with bacteria, but field-based evidence is limited to a few cases. The recently discovered plethora of subterranean diving beetle species in isolated aquifers in the arid interior of Australia offers a unique opportunity to evaluate alternative modes of speciation. This naturally replicated evolutionary ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 47 publications
2
55
0
Order By: Relevance
“…Considering the high level of genetic divergence found among our populations, we conclude that mitochondrial gene flow among these populations broke off completely sometimes in the past. This scenario is similar to what observed in subterranean diving beetles in isolated aquifers in Australia (Leijs et al 2012), but, quite unexpectedly, it is different from that retrieved for the only other Mediterranean cave crickets (genus Dolichopoda ). As a matter of fact,Allegrucci et al (2005) and Taylan et al (unpublished data) found strong evidence supporting isolation by distance pattern in Dolichopoda .…”
Section: Discussionsupporting
confidence: 82%
“…Considering the high level of genetic divergence found among our populations, we conclude that mitochondrial gene flow among these populations broke off completely sometimes in the past. This scenario is similar to what observed in subterranean diving beetles in isolated aquifers in Australia (Leijs et al 2012), but, quite unexpectedly, it is different from that retrieved for the only other Mediterranean cave crickets (genus Dolichopoda ). As a matter of fact,Allegrucci et al (2005) and Taylan et al (unpublished data) found strong evidence supporting isolation by distance pattern in Dolichopoda .…”
Section: Discussionsupporting
confidence: 82%
“…The aridification of the Australian continent, which deepened during the Late Pliocene following a wet–warm period in the early Pliocene (Sniderman et al ), may have favoured the evolutionary survival of aquatic beetle lineages with negative phototactic behaviour. Following the evolution of the three stygobitic Paroster species within the calcrete (Leijs et al ), we suggest that two of the species lost phototaxis, while it was retained in P. macrosturtensis . Similarly, the three Limbodessus species studied here have also likely lost phototaxis, conforming to the expected subterranean adaptations.…”
Section: Discussionmentioning
confidence: 63%
“…). These six species represent at least four independent evolutionary transitions from surface to subterranean environments: phylogenetic and modelling analyses suggest the Sturt Meadows species most likely evolved within the calcrete from a single common stygobitic ancestor that in turn evolved from a surface/interstitial species; the Laverton species each evolved independently from separate interstitial/surface species (Leys et al ; Leijs et al ). Various numbers of each species were collected and 20 individuals were selected from each group for the behavioural experiments, with the exception of L. palmulaoides as there were only 15 individuals available.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This model was also proposed to explain the evolution of Australian stygobitic dytiscid diving beetles in groundwater calcretes of central WA, with aridity from the late Miocene as the main driver for the transition to subterranean life (Leys et al, 2003). However, there is also evidence for speciation underground in this group (Leijs et al, 2012).…”
Section: Troglofauna: Climatic Relict and Adaptive Shift Hypotheses?mentioning
confidence: 95%